The roles of the big five personality traits and self-efficacy on individual entrepreneurial orientation towards technology readiness of Generation X, Generation Y, and Generation Z MSME owners in Metro Manila - Ferrera, Nicole Anne O. (Animo Repository, 2021)
Entrepreneurs need to be able to judge problems, take risks, innovate, adapt to current trends, and actively compete with the surrounding businesses to survive. With the growth of businesses and emergence of technological advancements yearly, it is crucial to examine how an entrepreneur’s age, personality, and mindset affect their readiness towards embracing new technologies. With the lack of local literature investigating the roles of psychological constructs on entrepreneurial decision-making, as well as the lack of literature exploring the influence of entrepreneurial orientation on one’s propensity to adopt technologies, this quantitative study aims to determine how the big five personality traits and self-efficacy affect the influence of individual entrepreneurial orientation towards technology readiness among Filipino entrepreneurs across different generational cohorts. With this, 150 Metro Manila-based MSME owners under the ready-to-consume food and beverage industry who belong to Generation X, Generation Y, and Generation Z were surveyed using an online questionnaire specifically designed for this study. In addition, three industry experts were interviewed to cross-validate the survey findings. After conducting mediation analysis, results highlighted that individual entrepreneurial orientation had a full mediating effect on the big five personality traits towards technology readiness, and a partial mediating effect on self-efficacy towards technology readiness. MSMEs under the food and beverage industry were recommended to design systems and policies that develop entrepreneurial orientation of all members by calculating risks, facilitating open and transparent communication, building a culture of trust and growth, recognizing competition, and integrating technologies into business operations.